Analysis of carbonaceous solid deposits from thermal stressing of FAMEs and FAME/diesel blends at different temperatures in a continuous flow reactor - Mandavha, Uyuenendiwannyi (Department of Mechanical Engineering, 2016)
Fuel deposits are carbon-rich high molecular weight species that are formed from the degradation of fuel. Diesel deposits may form on vital parts of a vehicle's engine or fuel system such as the fuel injectors. Once these deposits have formed, they can block the spray holes of the injector and may also cause moving parts within the injector to stick. Diesel deposits can cause engine failure, engine malfunction and affect engine performance. This study aims to investigate early stage deposits, formed in laboratory reactors, in particular a flow reactor. This was performed in order to gain insight into the processes by which these deposits form and what factors influence their formation. A flow reactor and closed sand bath reactor were employed to produce carbonaceous deposits, with the aim being that these might be similar to those formed in diesel injectors. The solid deposits were analysed using a Temperature Programmed Oxidation (TPO), Transmission Electron Microscopy (TEM) and Scanning Electron Microscopy (SEM). Soluble deposit precursors from the stressed fuels were assessed using ultraviolet visible spectroscopy (UV-Vis) and electrospray ionisation-mass spectroscopy (ESI-MS) in order to provide further insight into the chemical processes preceding deposit formation. The test fuels stressed in this study were an EN 590 reference diesel and two fatty acid methyl esters (FAMES), viz. rapeseed methyl ester (RME100) and soya methyl ester (SME100). Binary blends of 80 % EN 590 diesel and 20 %RME (RME20), 80 % EN 590 diesel and 20 % SME(SME20), 50 % EN 590 diesel and 50 % SME (SME50) and 93 % EN 590 diesel and 7 % SME (SME7) (v/v) were also investigated. Aerated fuels were thermally stressed at 300°C and 400°C for 5h in the presence of oxygen in a continuous flow reactor. This study represents the first application of the flow reactor methodology to systems that contain fatty acids methyl esters (FAMEs).